The Process of Setting the Parameters for Ensuring Passage of Oversized Cargos - Jan Petru; Vladislav Krivda (The Baltic Journal of Road and Bridge Engineering)
Engineering and the industry very often produce above-standard products concerning their dimensions and weights. There is often a problem with the transport of these products both within Europe and in subsequent transport all around the world. Because of these reasons, several projects to remedy the situation were implemented in the Czech Republic. The article describes the results of many years of research, which observed ensuring the passage of oversized cargos on roads. Further, the measurements, which were carried out, are presented in this paper − the measurement of an oversized vehicle using Global Positioning System devices, creation and modelling of missing cars in programs to verify the swept path, comparison of created models with the measurement using Global Positioning System devices.  Then the results of the implemented researches, the suggested parameters, and modelled cars are used for the suggestion of technical parameters of backbone network of roads. On these roads, the loads are transported. The results are also used for verification of critical points of the route, e.g. problematic places and intersections.